Dynamic Adjustment Strategy of Rail Guide Vehicle - Wenbin Liu (Hindawi Limited, 2021)
For the dynamic adjustment strategy of intelligent rail guide vehicle, the dynamic planning model has been built with the longest working time in the paper. In solving this problem, the longest target of the rail guide vehicles’ running time is converted to find the optimal moving path of the rail guide vehicles. Drawing on the shortest path idea, the model uses the Floyd algorithm and the simulated annealing algorithm. The longest running time of the rail guide vehicles in the model is the innovation point in the paper. When the rail guide vehicles path is optimal, when the rail guide vehicles is the busiest, the system is the most efficient.